2011
DOI: 10.1200/jco.2010.30.7744
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CD8+T-Cell Responses Against Novel Glioma–Associated Antigen Peptides and Clinical Activity by Vaccinations With α-Type 1 Polarized Dendritic Cells and Polyinosinic-Polycytidylic Acid Stabilized by Lysine and Carboxymethylcellulose in Patients With Recurrent Malignant Glioma

Abstract: Purpose A phase I/II trial was performed to evaluate the safety and immunogenicity of a novel vaccination with α-type 1 polarized dendritic cells (αDC1) loaded with synthetic peptides for glioma-associated antigen (GAA) epitopes and administration of polyinosinic-polycytidylic acid [poly(I:C)] stabilized by lysine and carboxymethylcellulose (poly-ICLC) in HLA-A2+ patients with recurrent malignant gliomas. GAAs for these peptides are EphA2, interleukin (IL)-13 receptor-α2, YKL-40, and gp100. Patients and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
444
3
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 522 publications
(462 citation statements)
references
References 53 publications
10
444
3
5
Order By: Relevance
“…The main difference from RANO is that iRANO advocates for additional confirmation scans if patients demonstrate PD within the first 6 months of initiating therapy and are neurologically stable. This window of observation was based on clinical data suggesting most immune-related changes appear to occur within the first 6 months of starting immunotherapy [58,59]; however, more investigations are necessary to truly understand the incidence of pseudoprogression in immunotherapies and the dependence of specific immune mechanisms on radiographic changes (e.g. active versus passive immunotherapies; checkpoint inhibitors versus vaccines; etc.).…”
Section: Immunotherapymentioning
confidence: 99%
“…The main difference from RANO is that iRANO advocates for additional confirmation scans if patients demonstrate PD within the first 6 months of initiating therapy and are neurologically stable. This window of observation was based on clinical data suggesting most immune-related changes appear to occur within the first 6 months of starting immunotherapy [58,59]; however, more investigations are necessary to truly understand the incidence of pseudoprogression in immunotherapies and the dependence of specific immune mechanisms on radiographic changes (e.g. active versus passive immunotherapies; checkpoint inhibitors versus vaccines; etc.).…”
Section: Immunotherapymentioning
confidence: 99%
“…14 Here, we have applied this method to isolate and analyze exosomes from plasma of patients with recurrent malignant glioma who were enrolled in a phase I/II clinical trial. The trial was performed at the University of Pittsburgh Cancer Institute 15 testing safety and efficacy of a novel vaccine which contained a-type1 polarized dendritic cells (aDC1) loaded with synthetic peptides specific for glioma-associated antigen (GAA) epitopes in combination with poly(I:C) and poly(ICLC). 15 The trial has demonstrated immunogenicity and clinical activity of this DC-based vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive necrosis along with a small rim of viable tumor was noted at subsequent autopsy at many of the metastatic sites including the brain lesion [40]. Along the same lines, anecdotal reports highlight the occurrence of pseudoprogression among brain tumor patients treated with a variety of vaccine regimens [38,[41][42][43].…”
Section: Complexity Of Radiographic Worsening Following Immunotherapymentioning
confidence: 88%
“…A growing number of clinical trials evaluating a wide array of immunotherapeutics across a spectrum of cancer indications demonstrate that a subset of patients treated with immunocytokines, cancer vaccines, T cell therapies and immune checkpoint inhibitors will achieve a radiographic response, durable stable disease or enhanced survival despite worsening of early imaging findings [21][22][23][30][31][32][33][34][35][36][37][38]. The most extensive experience derives from recent clinical trials investigating CTLA-4 and PD-1/PD-L1 immune checkpoint inhibitors which are currently being widely evaluated for multiple cancer indications.…”
Section: Complexity Of Radiographic Worsening Following Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation